"No place like home": Aging in post-reform Beijing. (July 2017) - Yu, Jie; Rosenberg, Mark W.
Abstract: This study shows the Western theorization and interpretation of aging, place and health are not well suited to a non-western case. The current generation of older Chinese has experienced the transition from a planned economy to a socialist market economy. Urban changes have taken place in various ways. This study explains the spatio-temporal processes of older people with their changing places by conducting in-depth interviews with 47 older people living at home in Beijing. Their generational consciousness and old place identities are deeply rooted in pre-reform Collectivism and shaped by socialist ideologies of the past. The representation of the old identity among older people is circumscribed by their living situations and selectively manifested. In most cases, there are limited mechanisms formed to recreate positive place meanings and reintegrate older people and place. The processes reflect the growing social inequality and changing cultural values in a society in transition. Growing social inequality and changing cultural values have a great impact on older people's health and well-being. Highlights: It challenges "aging in place" as a universal concept that Western theorizations are not well suited in a Chinese context. It advances the geographies of ageing literature by providing empirics from a non-Western context. It advances our conceptual understanding of the socio-political, cultural and historical dimensions of aging and place. People's coping strategies in places reflect the power relations and growing social inequality in a society in transition.